The Intellectual Impact on Extremist Movements: A Case Study of The Call for Global Islamic Resistance (Journal of the College of Education for Women, 2025)
The book “The Call for Global Islamic Resistance” is considered one of the most significant works in the history of extremist thought, due to several characteristics, most notably its encyclopedic nature. It presents a comprehensive and ready-to-implement plan for terrorists, both individuals and groups. The book has influenced several extremist organizations, most notably and dangerously, ISIS (Daesh). Its author, Abu Musab al-Suri (Mustafa Abdul Qadir), is regarded as one of the foremost and earliest leaders of modern terrorist organizations. The book was produced following over a quarter-century of field experience. This work is considered a vital document that reveals some of the psychological factors behind the formation of violent religious extremism discourse, primarily through the concept of an eschatological worldview. As for the research methodology, qualitative content analysis was adopted, as it is one of the methods used in discursive social psychology. This approach was deemed most suitable for dealing with such an important and voluminous document.